16‐2: Distinguished Paper: Thin and Low‐Reflection Metal Black Matrix for High PPI LCD. Issue 1 (28th June 2022) - Yoshida, Keisuke; Ueda, Satoshi; Hachiya, Atsushi; Okada, Kuniaki; Hirai, Akira; Kawahira, Yuichi; Misaki, Katsunori; Furukawa, Hiroaki; Kato, Hiromi
Abstract : A 2.9‐inch 2K2K (1058 ppi) panel using low‐reflection metal black matrix (BM) has been developed. We confirmed lower surface reflectance of LCD by using low‐reflection metal BM, and confirmed that there was no adverse effect on the display optical characteristics. We have shown that a thinner BM allows us to design more transparent pixels by increasing the aperture ratio, or to increase the color viewing angle. This technique can also be applied to Flip panel structures.